2003
DOI: 10.1073/pnas.252779099
|View full text |Cite
|
Sign up to set email alerts
|

Negative specific heat of a magnetically self-confined plasma torus

Abstract: It is shown that the thermodynamic maximum-entropy principle predicts negative specific heat for a stationary, magnetically selfconfined current-carrying plasma torus. Implications for the magnetic self-confinement of fusion plasma are considered.T he goal of the controlled thermonuclear fusion program is to make the energy source that powers our sun available to human society. Deep in our sun's interior, favorable conditions for the quasistationary nuclear burning of the solar plasma prevail as a result of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 38 publications
(61 reference statements)
1
45
1
Order By: Relevance
“…Due to this property, at statistical equilibrium, inequivalence between the microcanonical and the canonical ensembles is a generic feature. This was first observed in models of self gravitating stars [2,3], and then seen in a number of other models ranging from the point vortex model [4,5], plasma physics [6], self gravitating systems [7,8], two dimensional flows [9], long range Hamiltonian models [10,11] to simple spin models with mean field interactions [12,13]. A classification of phase transitions and ensemble inequivalence in generic long range systems [14] has shown that many possible types of behavior remain to be seen in specific physical systems.…”
Section: Introductionmentioning
confidence: 92%
“…Due to this property, at statistical equilibrium, inequivalence between the microcanonical and the canonical ensembles is a generic feature. This was first observed in models of self gravitating stars [2,3], and then seen in a number of other models ranging from the point vortex model [4,5], plasma physics [6], self gravitating systems [7,8], two dimensional flows [9], long range Hamiltonian models [10,11] to simple spin models with mean field interactions [12,13]. A classification of phase transitions and ensemble inequivalence in generic long range systems [14] has shown that many possible types of behavior remain to be seen in specific physical systems.…”
Section: Introductionmentioning
confidence: 92%
“…It was formulated in a simple way in [104] and reference [41] showed a corresponding equivalence of canonical transformations and of changes of gauge. 30 For instance the existence of negative specific heat in a magnetically self-confined plasma torus [84]. The saturation of the cold and water-bag beam-plasma instability can be computed analytically by using Hamiltonian (1) introduced in section III with a single wave (cold: [70], water-bag: [8,9]).…”
Section: A Limited Capabilities Of Modelsmentioning
confidence: 99%
“…Many physical systems show a change in the concavity of the entropy as a function of the energy with important thermodynamic implications (star, isolated clusters, cluster of 147 sodium atoms, Ar39 cluster, small systems, finite quantum systems, magnetically self-confined plasma [1][2][3][4][5][6][7]). The concavity's point of change-the inflection point-becomes directly related to the divergence of the specific heat.…”
Section: Introductionmentioning
confidence: 99%